Successful Use of Aspirin, Apixaban, and Viscoelastography in a Patient with Severe COVID Disease and Allergy to Porcine Products. (February 2022) - Reeder, Jacob A.; Reynolds, Tessa R.; Gilbert, Brian W.
Coagulation abnormalities are frequently described in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Common thromboprophylaxis and anticoagulation treatment strategies include the use of heparinoid therapy. We describe a 57-year-old woman with an allergy to porcine products that was started on apixaban for anticoagulation therapy given her allergy profile and need for venous thromboembolism prophylaxis. Apixaban and aspirin therapy were optimized with the support of serial viscoelastography and platelet function assays. Our patient experienced respiratory failure requiring intubation for 7 days but was successfully weaned to room air, tolerated a regular diet, and ultimately discharged to home after a 17-day hospital course. Here we report the safe and successful use of aspirin, apixaban, and viscoelastography for COVID-19-associated coagulopathy.